An Analysis of the Relationships & Views Among the Big Five Personality Traits and Kolb’s Learning Approaches in Higher Education Students in Dubai, UAE - ALAMEEN, MOHAMMED ADNAN (2024)
In this study, the interplay between personality traits and learning approaches among higher education students in Dubai, United Arab Emirates is explored, using the Big Five Personality Traits and Kolb's Experiential Learning Theory as theoretical frameworks. Conducted at a renowned semi-governmental institution, this mixed-methods research utilized quantitative surveys with 186 students and qualitative interviews with 19 students. Quantitative data were analysed to identify correlations between personality traits (Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism) and learning approaches (learning modes: Concrete Experience, Reflective Observation, Abstract Conceptualization, and Active Experimentation; and learning styles: Accommodating, Assimilating, Diverging, and Converging). Qualitative interviews provided deeper insights into these relationships. Major quantitative findings indicated significant correlations between traits like Agreeableness and Openness with Active Experimentation and Reflective Observation learning modes, as well as Conscientiousness with Abstract Conceptualization and Concrete Experience modes. Qualitative data revealed that students with high Agreeableness and Openness preferred reflective and experiential learning activities, while those with high Conscientiousness thrived in structured and conceptual tasks. These insights highlight the potential for personalized teaching strategies. These results suggest that incorporating personality traits into educational settings can optimize learning outcomes by aligning teaching methods with students’ learning preferences. The study emphasizes the necessity for further research across various educational settings to validate and expand upon these findings, aiming to enhance educational effectiveness through tailored pedagogical approaches.